Evaluating the potential of electrolysed water for the disinfection of citrus fruit in packinghouses - Dilarri, Guilherme [UNESP]; Zamuner, Caio FC [UNESP]; Mendes, Carolina R [UNESP]; Junior, José RM [UNESP]; Morão, Luana G [UNESP]; Montagnolli, Renato N; Bidoia, Ederio D [UNESP]; Ferreira, Henrique [UNESP] (Wiley, 2021)
BACKGROUND: The largest and most profitable market for citrus is the production of fresh fruit. Xanthomonas citri subsp. citri is a Gram-negative plant pathogen and the etiological agent of citrus canker, one of the major threats to citrus production worldwide. In the early stages of infection, X. citri can attach to plant surfaces by means of biofilms. Biofilm is considered an essential virulence factor, which helps tissue colonization in plants. Thus, sanitization of citrus fruit is mandatory in packinghouses before any logistic operation as packing and shipment to the market. The aim of this study was to evaluate electrolysed water (EW) as a sanitizer for the disinfection of citrus fruit in packinghouses. RESULTS: Using a protocol to monitor cell respiration we show that EW, obtained after 8 and 9 min of electrolysis, sufficed to kill X. citri when applied at a concentration of 500 μL mL−1. Furthermore, microscopy analysis, combined with time-response growth curves, confirmed that EW affects the bacterial cytoplasmatic membrane and it leads to cell death in the first few minutes of contact. Pathogenicity tests using limes to simulate packinghouse treatment showed that EW, produced with 9 min of electrolysis, was a very effective sanitizer capable of eliminating X. citri from contaminated fruit. CONCLUSION: It was possible to conclude that EW is significantly effective as sodium hypochlorite (NaClO) at 200 ppm. Therefore, EW could be an alternative for citrus sanitization in packinghouses. © 2020 Society of Chemical Industry.
Keywords: electrolysed water; lime; membrane permeabilization; sanitizer; Xanthomonas citri subsp. citri